Psychological and Behavioral Impact: Exploring Gaslighting to Control Woman in Romantic Relationship Using Speech Acts Theory - Istiqomah, Adilah Al; Rakhmawati, Fitri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Gaslighting is a form of emotional manipulation that significantly affects a victim’s mental health, leading to confusion, anxiety, depression, and emotional instability. This study analyzes the psychological and behavioral impacts of gaslighting in romantic relationships using Austin’s speech act theory, which includes locutionary, illocutionary, and perlocutionary acts. The analysis focuses on the interaction between the characters Mark and Alicia in the film Your Reality. Data were collected through qualitative analysis of selected dialogues. The findings show that expressive illocutionary acts are the most dominant (37.50%), followed by directives (29.17%), representatives (20.83%), and commissive (12.50%). Psychologically, the most prevalent impact is anxiety (61.11%), reflected in feelings of guilt (22.22%), confusion (16.67%), self-doubt (11.11%), and low self-esteem (11.11%). Depression also appears (5.56%) through feelings of distress. Behaviorally, gaslighting leads to increased obedience and submission (33.34%), seen in over-apologizing (5.56%), prioritizing the gaslighter needs (11.11%), and loss of personal autonomy, such as difficulty making decisions (11.11%). These findings reveal how gaslighting shapes emotional dependency and restricts victims’ ability to act independently. The study highlights the importance of recognizing gaslighting tactics in order to restore autonomy, improve mental health, and break cycles of manipulation in romantic relationships.